Kinerja Tukang dan Laden Pada Proyek Pembangunan Gedung - Dewi Fameilia; Rini Ratnayanti; Bernardinus Herbudiman (Universitas Lambung Mangkurat, 2004)
On the same quality standard, performance of contractors can be observed in the time and cost parameters. These parameters are directly influenced by the productivity of workers. Productivity is generally a ratio of work result to the available resources. Observation was conducted to the productivity of foremen, workers, and laborers who were all the frontline construction executors. The work scope was limited to reinforced concrete, which is typically used for building construction. Malls type was chosen due to wide development of this type as economical centre in Bandung.Case study was conducted to the mall inside the City Square complex, in Abdurrachman Saleh street, Bandung. Data gathering was done by using the record of weekly work development report signed by project manager contractor and supervisor consultant. Observation was directly done to a number of workers per work sub-item per day. Productivity analysis was conducted according to the data and observation results.Productivity is influenced by supervision, coordination, internal, and inter-group factors. This research resulted the productivity coefficient value of foreman, workers, and laborers, which later will be used as a cost calculation reference of malls project.